Respuesta :

Answer:

A, B, D, F

Step-by-step explanation:

Given expression: [tex]8^{\frac23}[/tex]

Apply exponent rule [tex]a^{bc}=(a^b)^c[/tex]

[tex]\implies 8^{\frac23}=(8^2)^{\frac13}[/tex]

Apply exponent rule [tex]a^{\frac{1}{n}}=\sqrt[n]{a}[/tex]

[tex]\implies (8^2)^{\frac13}=\sqrt[3]{8^2}[/tex]

Therefore, option A

Apply exponent rule [tex]a^{bc}=(a^b)^c[/tex]

[tex]\implies 8^{\frac23}=(8^{\frac13})^2[/tex]

Apply exponent rule [tex]a^{\frac{1}{n}}=\sqrt[n]{a}[/tex]

[tex]\implies (8^{\frac13})^2=(\sqrt[3]{8})^2[/tex]

Therefore, option B

Apply exponent rule [tex]a^{bc}=(a^b)^c[/tex]

[tex]\implies 8^{\frac23}=(8^{\frac13})^2[/tex]

As [tex]8^{\frac13}=2[/tex]

[tex]\implies (8^{\frac13})^2=2^2[/tex]

Therefore, option D

Apply exponent rule [tex]a^{bc}=(a^b)^c[/tex]

[tex]\implies 8^{\frac23}=(8^{\frac13})^2[/tex]

As [tex]8^{\frac13}=2[/tex]

[tex]\implies (8^{\frac13})^2=2^2[/tex]

[tex]\implies 2^2=4[/tex]

Therefore, option F